Effect of Various Gelling Cations on the Physical Properties of "Wet" Alginate Films. Issue 4 (24th February 2014) - Harper, B. Allison; Barbut, Shai; Lim, Loong‐Tak; Marcone, Massimo F.
Abstract In this study, the physical properties of "wet" alginate films gelled with various divalent cations (Ba2+, Ca2+, Mg2+, Sr2+, and Zn2+) were explored. Additionally, the effect of adding NaCl to the alginate film‐forming solution prior to gelling was evaluated. Aside from Mg2+, all of the divalent cations were able to produce workable "wet" alginate films. Films gelled with BaCl2 (without added NaCl) had the highest (P < 0.05) tensile strength and Young's modulus while films gelled with CaCl2 (alone) had the highest puncture strength. The Zn‐alginate and Sr‐alginate films had the highest elongation at break values. Adding NaCl to the alginate film‐forming solution increased the viscosity of the solution. Films with added NaCl were less transparent and had lower tensile strength, elongation, and puncture strength than films formed without NaCl in the film‐forming solution. ATR‐FTIR results showed a slight shift in the asymmetric COO− vibrational peak of the alginate when the "wet" alginate films were gelled with Zn2+.